Pengaruh Gaya Kepemimpinan Demokratis, Sistem Informasi dan Kaizen 5S terhadap Kinerja Karyawan pada Alfamidi Cabang Sidoarjo - Sangjaya, Handeka Setya Putra; Andriani, Dewi; Abadiyah, Rifdah (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine and test how much influence democratic leadership style, information systems, and 5S kaizen have on employee performance at Alfamidi Sidoarjo Branch. Data collection through questionnaires with simple random sampling techniques with a minimum of 167 respondents. This research method uses multiple linear regression. The results of the study indicate that simultaneously there is a positive and significant influence between the variables of democratic leadership style, information systems and 5S kaizen on employee performance at Alfamidi Sidoarjo Branch. However, partially only the 5S kaizen variable does not affect employee performance at Alfamidi Sidoarjo Branch.